2023
DOI: 10.1007/s10796-023-10385-7
|View full text |Cite
|
Sign up to set email alerts
|

Relating Social Media Diffusion, Education Level and Cybersecurity Protection Mechanisms to E-Participation Initiatives: Insights from a Cross-Country Analysis

Abstract: Virtual Social Networks (VSN) act as a catalyst for the success of the active participation of citizens in information sharing, collaboration, and decision making. VSN based e-participation tools allow many-to-many communication and collaboration near real-time with users who might be in geographically dispersed locations. It provides a platform to voice opinions and perspectives and share them with others in new and innovative ways. Cybersecurity is a key area that needs to be considered for the success and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…In terms of accountability, research by Berliner et al [ 29 ] revealed public demands for government transparency and accountability mechanisms, while Fan and Meng [ 30 ] demonstrated that effective governance mechanisms can enhance the quality and utilization of open data, strengthening government accountability. Ahangama [ 31 ] explored the role of social media in enhancing public participation and the accountability process. Research by Ji and Kim [ 32 ] focused on the public demands for regulatory intervention in the age of social media, analyzing how the public influences the formation of regulatory policies during corporate crises through social media.…”
Section: Related Workmentioning
confidence: 99%
“…In terms of accountability, research by Berliner et al [ 29 ] revealed public demands for government transparency and accountability mechanisms, while Fan and Meng [ 30 ] demonstrated that effective governance mechanisms can enhance the quality and utilization of open data, strengthening government accountability. Ahangama [ 31 ] explored the role of social media in enhancing public participation and the accountability process. Research by Ji and Kim [ 32 ] focused on the public demands for regulatory intervention in the age of social media, analyzing how the public influences the formation of regulatory policies during corporate crises through social media.…”
Section: Related Workmentioning
confidence: 99%
“…The provision of computing services via the internet, such as infrastructure as a service (IaaS), platform as a service (PaaS), and software as a service (SaaS), is known as cloud computing. Without requiring a significant infrastructure investment, cloud computing gives businesses on-demand access to scalable computing resources, storage, and apps (Ahangama, 2023). Initiatives to leverage digital technologies to improve corporate operations, improve consumer experiences, and spur innovation are driven by information technology.…”
Section: Figure 1 Information Technologymentioning
confidence: 99%
“…However, it does face severe challenges in the face of cybersecurity concerns. The paper by Ahangama (2023) that we selected for this special issue studies the role played by virtual social networks in a country in impacting the level of e-participation by the citizens of the country in governmental services. Using data collected from 115 countries the author shows that cybersecurity protection mechanisms and the level of education of citizens play a significant role in influencing e-participation.…”
Section: Introductionmentioning
confidence: 99%